Remoção do pesticida 2,4-D em meio aquoso através do processo de coagulação e do uso da casca da Moringa oleifera como biossorvente - Janz, Fellipe Jhordã Ladeia (2021)
Brazil is one of the largest consumers of pesticides in the world due to mechanized monoculture production that requires chemical products to control pests. The herbicide 2,4- Dichlorophenoxyacetic acid (2,4-D (C8H6Cl2O3)) is one of the most commercialized in Brazil due to its good efficiency, low cost and authorization for application in different crops. With the constant use of chemical products in agriculture, the concern of possible impacts on the environment has arisen, due to the presence of this product in soil, surface and underground waters. In order to remove the herbicide from the water to minimize impacts, the ability of different techniques to remove pesticides from water has been evaluated. This study aims to evaluate the removal of 2,4-D through the coagulation process using the coagulants aluminum sulfate, ferric chloride, tannin and Moringa oleifera and through adsorption with Moringa oleifera seed shell. The study was separated into two steps, the first one being focused on the coagulation process and the second one on the adsorption process with the biosorbent made with the seed husk of Moringa oleifera. The study of the first stage was carried out in Jar-Test simulating the processes that occur in the water treatment plants, also evaluating the effect of the variation in the coagulant dosages from 0.25 to 10 mg.L-1 and with pH (4 , 7 and 10). Organic coagulants showed maximum removal efficiency of less than 5% in all situations analyzed for the evaluation of pH and concentration. The use of aluminum sulfate coagulant with pH 7 demonstrated efficiency ranging from 5% to 11% depending on the concentration. The ferric chloride at the lowest concentrations showed removal of up to 24% at pH 4 and up to 16% at pH 7. In the second step, the adsorbent from the seed husk of Moringa oliefera was used and the adsorption capacity was evaluated. Using the experimental design of Plackett and Burman, the effects of pH, stirring speed and mass amount of the adsorbent were considered, thus defining the best condition for these parameters as 0.02g of adsorbent, stirring speed of 180 rpm and pH 4. Then, the kinetics test was performed, obtaining a reaction equilibrium time of 720 minutes. When considering the effect of varying the 2,4-D concentration and temperature, it was observed that increasing the temperature did not improve efficiency, indicating that the process is exothermic and that the Langmuir isotherm is the one that best fits the data experimental tests. Through the results obtained in the study, it was concluded that the removal of 2,4-D through the coagulation process when organic coagulants were applied was not efficient, and when inorganic coagulants were used, they presented low contaminant removal. The adsorption process with Moringa oleifera bark biosorbent proved to be very efficient with a maximum adsorption capacity of 130.79 mg.g-1 , being an alternative for the treatment of water contaminated with 2,4-D.